Determinants of Switching Barriers among Oman’s Retail Banking Consumers - KIRAN, FAIZA; IBRAHIM, DR. NORHAZLINA BINTI; SHAHARUDDIN, PROF. MADYA DR. AMIR BIN (The journal of contemporary issues in business and government, 2021)
This study examines the impact of switching barriers comprises of complexity, switching cost, locked-in, and apathy on the switching decision. The data were collected through a survey questionnaire from three cities (Muscat, Salalah, and Sohar) with a sample of 420 respondents. The participants were Omani nationals only. The data were analyzed using Structural Equation Modelling (SEM) Analysis using SPSS and AMOS software. The data were tested for the normality, descriptive analysis, reliability, correlation, exploratory Factor Analysis (EFA) and Confirmatory Factor Analysis (CFA). The result of the switching barriers indicates that apathy fail to influence the negative relationship with switching decision. However, switching cost, complexity and locked in had a negative impact on the decision to switch that creates barriers among the customers while switching from conventional banking to Islamic banking system. The study concludes that the government, management, and Shariah board of the Islamic banks should focus on establishing a robust and dynamic Islamic banking, which caters for customers’ needs. Finally, Islamic banking products and service, financial and non-financial strategies should address the customers’ financial needs and provide comprehensive banking services.